Strategies for Autonomous Learning of English as L2 of Pre-Intermediate English Courses at UGC and ESIDE - Yury Andrea Yepes Landinez; Johanna Alexandra Barragán Arias; Óscar Fabián Pulido Rodríguez (Universidad Pedagógica Nacional Francisco Morazán, 2023)
This research on the autonomous learning of English as a second language (L2) was carried out in conjunction with pre-intermediate English students from La Gran Colombia University (UGC) and the School of Languages and Dialects of the National Army (ESIDE). The main objective was to implement the autonomous learning strategies of English as a L2 in the population sample. Initially, a review of background information related to the theoretical bases was carried out, for which the following categories of analysis were established: Autonomous Learning, Competencies and Abilities, Metacognition and New Technologies of English. The methodology used was mixed with a quantitative predominance under a quasi-experimental design, and we worked with an intentional probabilistic sample. All of the above was carried out through the implementation of instruments such as a competency level pre-test, a semi-structured questionnaire and a post-test, which allowed the results to be contrasted and analyzed. Finally, the results show that more than half of the population obtained academic improvement thanks to the implementation of 27 strategies for autonomous learning of English. Likewise, the adoption of an autonomous culture in their academic and professional lives is evident.